2008
DOI: 10.1002/jts.20288
|View full text |Cite
|
Sign up to set email alerts
|

Avoidant coping and PTSD symptoms related to domestic violence exposure: A longitudinal study

Abstract: The impact of avoidant coping on level of PTSD symptoms over 1 year was examined among 262 women exposed to intimate partner violence (IPV) within the past month. Covariates included childhood sexual abuse (CSA), IPV severity, perceived and formal social support, and revictimization. Using longitudinal hierarchical multiple regression, avoidant coping was found associated with PTSD symptoms at 1-year follow-up, controlling for initial symptoms and covariates. Revictimization also had long-term consequences bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
150
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(171 citation statements)
references
References 43 publications
15
150
1
4
Order By: Relevance
“…The presumably high stress of the ICU experience, influenced in part by the outcome of the patient, mobilizes coping strategies. The use of avoidant coping in response to ongoing ICU and post-ICU stressors may play a role in sustaining and accelerating PTSD symptom severity as has been shown in other traumatic stress populations (27,51,53). Problem-focused coping has been associated with negative psychological health outcomes from acute stress-ors but positive health outcomes with chronic stressors, suggesting psychological difficulty in the short term but improved psychological adjustment in the long term (22,26,36).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…The presumably high stress of the ICU experience, influenced in part by the outcome of the patient, mobilizes coping strategies. The use of avoidant coping in response to ongoing ICU and post-ICU stressors may play a role in sustaining and accelerating PTSD symptom severity as has been shown in other traumatic stress populations (27,51,53). Problem-focused coping has been associated with negative psychological health outcomes from acute stress-ors but positive health outcomes with chronic stressors, suggesting psychological difficulty in the short term but improved psychological adjustment in the long term (22,26,36).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 97%
“…Positive associations between coping strategies and PTSD symptoms have been described in other PTSD populations with avoidant coping having the strongest positive association with PTSD symptoms (26,27,36,48,49). Some authors have presumed the presence of PTSD symptoms causes the use of avoidant coping (36, 50).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the well-known relationship between even a single traumatic event and the development of PTSD or other psychiatric problems 39 is strengthened following multiple occurrences of trauma, particularly physical assaults. 8,40 For drug users who are not in treatment, the occurrence of new traumatic events is likely to destabilize progress toward healthy behavior change by intensifying psychiatric and drug use severity, 8,17,41 which, in turn, increases risk of further traumatic event exposure. Future studies should assess the mental health outcomes related to these very high re-exposure rates, with particular attention to the greater risk for women injecting drug users.…”
Section: Implications Of Traumatic Event Re-exposurementioning
confidence: 99%
“…Studies have shown that avoidant coping is positively associated with higher symptoms of PTSD (Krause, Kaltman, Goodman, & Dutton, 2008;Ullman, Townsend, Filipas, & Starzynski, 2007). With the use of military/veteran samples, studies have further supported the notion that the use of avoidant coping strategies during deployment is positively correlated with a later PTSD diagnosis (Benotsch et al, 2000;Solomon, Mikulincer, & Flum 1988;Stein et al, 2005;Wolfe et al, 1993).…”
Section: Ptsd Symptomatology and Treatment Historymentioning
confidence: 94%